A randomized controlled trial comparing hydrophilic coated to uncoated polyurethane double J stents: Does it impact stent-related symptoms? - Gaurav Sharma; Naveen Kumar; Diptiranjan Bai; Sachin Patel; Dilip Kumar Mishra; Anurag Yadav; Madhu Sudan Agrawal (Indian Journal of Urology)
Introduction: Advancements in stent materials and designs are aimed at improving stent-related morbidities, lower urinary tract symptoms (LUTSs), pain, and compromised quality of life (QoL). Various stent materials and coatings have been investigated for their impact on stent-related symptoms. This prospective randomized study aimed to compare urinary symptoms and QoL in patients with polyurethane double J (DJ) stents, with or without hydrophilic polyvinylpyrrolidone coating. Materials and Methods: Sixty adult patients undergoing endourological procedures and DJ stent placement were randomized into two groups in 2:1 ratio. In 20 patients, polyurethane stents with hydrophilic coating and in 40 patients, stents without hydrophilic coating were placed. In all patients, a stent of 5F diameter and 26 cm length was used. Urinary symptoms, pain, and QoL were assessed at the time of stent removal, i.e., at 3–4 weeks using the validated ureteral stent symptom questionnaire (USSQ). Results: The demographic data were comparable in both groups. Patients with hydrophilic stents reported significantly fewer urinary symptoms (mean score 10.75 vs. 15.28, P < 0.001), lower pain scores (1.50 vs. 3.18, P < 0.001), and better QoL scores (3.0 vs. 5.23, P < 0.001). Symptoms such as frequency, nocturia, urgency, and burning micturition were notably reduced in the hydrophilic group. In addition, 60% of patients in the hydrophilic group reported no pain compared to only 7.5% in the nonhydrophilic group (P < 0.001). Conclusion: Hydrophilic-coated DJ stents significantly alleviate LUTS and improve QoL, warranting further large-scale research to validate these findings. These findings align with previous studies suggesting that hydrophilic coatings improve stent-related outcomes.